SPEED (SPlEnic Embolisation Decisions) study—Decision to treat acute traumatic splenic artery injury in the context of trauma protocol - Paul Jenkins; Jim Zhong; James Harding; Lexy Sorrell; Jason Smith; Victoria Allgar; Carl Roobottom (PLoS ONE, 2025)
Background The spleen is commonly injured in trauma and this may be managed with a conservative approach, embolisation or splenectomy. There is uncertainty how splenic embolisation fits into the treatment paradigm and the delivery of IR services remains variable. Aims and objectives The primary objectives are to determine if service design significantly affects splenic embolisation (SE) rates in AAST grade 2–5 acute traumatic splenic injuries (ATSI) across the Major Trauma Centres (MTCs) in England and to determine if variation in treatment affects SE outcomes in ATSI. Methods We will include 5 years of data from traumatic splenic injury patients in the MTCs from 01/01/2016 to 31/12/2020 available from the Trauma Audit and Research Network (TARN) database. Inclusion Criteria will be all patients with ATSI registered with TARN. Those without a CT available to grade radiologically will be excluded. Data available from the TARN database and then correlated with data that will be collected at each MTC, where detail as to the embolisation technique, specific injury pattern, imaging based follow up and patient survival will be available. A short service-based questionnaire will be sent to each centre to establish centre-specific details such as on call rota, IR response activation, reporting practices and capture data around routine decision-making at that site. Data will be collected on an anonymised (REDCap) database. This project will evaluate the impact of service design on embolisation rates and outcomes, as well as evaluating the impact of the variation upon treatment selection and outcomes. Logistic regression will be used to identify factors associated with treatment selection and mortality at 30 days.